Stepwise redox changes alter the speciation and mobilization of phosphorus in hydromorphic soils. (February 2022) - Shaheen, Sabry M.; Wang, Jianxu; Baumann, Karen; Ahmed, Ashour A.; Hsu, Liang-Ching; Liu, Yu-Ting; Wang, Shan-Li; Kühn, Oliver; Leinweber, Peter; Rinklebe, Jörg
Abstract: Sustainable engineering and management of hydromorphic arable soils need deep knowledge about the redox-mediated interactions between nutrients and soil colloids. Consequently, we examined the redox-mediated interactions of P with metal oxides and organic carbon (OC) in toe-, mid-, and upper-slope arable soils under dynamic redox changes using geochemical (biogeochemical microcosm), spectroscopic (XANES), and molecular (quantum chemical calculations (QCC)) approaches. We controlled the redox potential (EH ) in two directions i.e., 1) slowly oxidizing direction (SOD; EH increased from −286 to +564 mV); and 2) slowly reducing direction (SRD; EH decreased from +564 to −148 mV). In the SOD of all soils, P, Fe 2+ and OC mobilized at EH  ≤ 200 mV, due to the pH decrease from 7.2 to 4.1 and dissolution of Fe-oxyhydroxides/carbonates, as indicated by the decrease of Fe–P and Ca–P determined by P– K -edge-XANES. At EH  > 200 mV, P immobilized due to the strong P binding with Fe 3+ as suggested by QCC. In the SRD of mid-slope-soil, P immobilized with decreasing EH, due to pH increase and P retention by aromatic carbon and/or precipitation by carbonates, as supported by increase of organic-P and Ca–P. These findings help for management of P in arable soils. Graphical abstract: Image 1 Highlights: Stepwise and repeated redox cycles alter P speciation and affect its mobilization. P, Fe 2+ and DOC mobilized under low EH in toe-, mid-, and upper-slope arable soil. Acidic/reductive dissolution of Fe-oxide/carbonate governed P release under low EH . Aromatic carbon compounds governed P release under high EH in upper slope soil. Fe–P and Ca–P decreased under low EH and organic-P and Ca–P increased under high EH .